Polysaccharide conjugates surpass monosaccharide ligands in hepatospecific targeting – Synthesis and comparative in silico and in vitro assessment. (November 2021) - Dhawan, V.; Joshi, G.; Sutariya, B.; Shah, J.; Ashtikar, M.; Nagarsekar, K.; Steiniger, F.; Lokras, A.; Fahr, A.; Krishnapriya, M.; Warawdekar, U.; Saraf, M.; et al.
Abstract: Ligands with the polysaccharide headgroups have been recently reported by our group to possess enhanced interaction with asialoglycoprotein receptor (ASGPR) in silico as compared to ligands having galactose moieties. This enhanced interaction is a result of the polymer's backbone support in anchoring the ligand in a specific orientation within the bilayer. In this paper, we have attempted to provide an in vitro proof of concept by performing a comparative evaluation of polysaccharide and monosaccharide-based ligands. Docking was performed to understand interaction with ASGPR in silico . Agarose and galactose conjugates with behenic acid were synthesized, purified, and characterized to yield biocompatible hepatospecific ligands which were incorporated into nanoliposomes. Cellular internalization of these targeted liposomes was studied using confocal microscopy and flow cytometry. The toxicity potential was assessed in vivo . Results indicated that the polysaccharide-based ligand increased cellular uptake due to better interaction with the receptor as compared to ligand bearing a single galactose group. In addition to developing novel liver targeting ligands, the study also established proof of concept that has been suggested by earlier in silico investigations. The approach can be used to design targeting ligands and develop formulations with improved targeting efficacy. Graphical abstract: Image 1 Highlights: Design and one pot synthesis of biocompatible monosaccharide and polysaccharide based fatty acid esters. Development, characterization and comparative assessment of cellular uptake of targeted liposomes. Validation and establishing proof of concept of enhanced targeting efficacy of polysaccharide-based ligands. Development of biocompatible platform for hepatospecific delivery.